Drug-resistant HER2-positive breast cancer: Molecular mechanisms and overcoming strategies - Wu, Xiaofan; Yang, Hongjian; Yu, Xingfei; Qin, Jiang-Jiang (Frontiers in Pharmacology, 2022)
Breast cancer is one of the most common malignancies and the leading cause of cancer-related death in women. HER2 overexpression is a factor for poor prognosis in breast cancer, and anti-HER2 therapy improves survival in these patients. A dual-targeted combination of pertuzumab and trastuzumab, alongside cytotoxic chemotherapy, constitutes the primary treatment option for individuals with early-stage, HER2-positive breast cancer. Antibody-drug conjugate (ADC) and tyrosine kinase inhibitors (TKI) also increase the prognosis for patients with metastatic breast cancer. However, resistance to targeted therapy eventually occurs. Therefore, it is critical to investigate how HER2-positive breast cancer is resistant to targeted therapy and to develop novel drugs or strategies to overcome the resistance simultaneously. This review aims to provide a comprehensive discussion of the HER2-targeted agents currently in clinical practice, the molecular mechanisms of resistance to these drugs, and the potential strategies for overcoming resistance.